The Figure of the Good Thief and Conversion in extremis in Late Medieval Preaching - Hanska, Jussi (Medieval sermon studies, 2023)
The Good Thief mentioned in Luke 23. 29-43 is an extreme example of the benefits of conversion. Yet he was not presented as an archetype of the penitent sinner; rather, that role was reserved for Mary Magdalene. This article studies the very few cases where the Good Thief, or St Dismas as he was also known, was discussed in medieval sermons. It also endeavours to explain the reasons why he was not considered a suitable role model for the penitent sinner. The discussion revolves around the contradictory requirements of the preachers. On one hand, they wanted to avoid driving sinners to despair by encouraging them to convert even if at the very end of life. On the other hand, they needed to emphasize the need to do penance now rather than postpone it for an uncertain future. This latter need was considered more important and that proved to be a crucial argument against using the Good Thief as an exemplary figure in the sermons.